How Important Is the Financial Media in Global Markets? - Griffin, John M.; Hirschey, Nicholas H.; Kelly, Patrick J. (Review of Financial Studies, 2011)
This article studies differences in the information content of 870,000 news announcements in 56 markets around the world. In most developed markets, a firm's stock price moves much more on days with public news about the firm. In contrast, in many emerging markets volatility is similar on news and non-news days. We examine several hypotheses for our findings. Cross-country differences in stock price reactions are best explained by insider trading, followed by differences in the quality of the news dissemination mechanism. Our findings are useful for quantifying the extent of insider trading and how the financial media affects international markets.